Ta`līm Muhadatsah Bi Thuruqi at-Tamṡīl Li Tarqiyyah Qudrah aṭ-Ṭalabah `Alā at-Takallum Bi al-Lughah al-`Arabiyyah : (Dirāsah Tajrībiyyah Bi Ma`had Bābun-Najāḥ al-`Aṣrī Banda Aceh) - Zikrullah, Zikrullah (STAI Nusantara Kota Banda Aceh, 2023)
The method of dialog (conversational Method) is one method of teaching foreign languages such as Arabic, English, or other languages by directly inviting students to dialogue/speak with the foreign language being taught. Playing drama is one way to make it easier for students to remember Arabic vocab. The conversational method intended here is a way of teaching by dramatizing behavior in the form of social relations. As for the problems that researchers encounter at the modern Babun Najah boarding school, some students at the Modern Pesantren Babun Najah are less able to understand the language when dialoguing with Arabic with their friends well and it is also difficult to pronounce the Arabic language. From these problems, the researcher wants to discuss research entitled